Modeling the impacts of constant price GDP and population on CO2 emissions using Cobb-Douglas model and ant colony optimization algorithm - Hafizan, Juahir; Sukono, .; Subartini, B; Thalia, P; Supian, S.; Lesmana, E; Budiono, R (2019)
The per capita Gross Domestic Product (GDP) measures a country's economic growth. Increasing GDP is a dream of all countries, but generally, GDP increases often have a negative impact with increasing CO emissions. This paper intends to model the impact of GDP growth based on constant prices and the population in increasing CO emissions in Indonesia. Modeling is done by using Cobb-Douglas model production function, where parameter estimation is done by using ant colony optimization algorithm. Furthermore, model estimators are used for forecasting CO emission concentrations. The results of the analysis show that the impact of GDP based on constant prices and population significantly follows the Cobb-Douglas model of production, with the coefficient of elasticity is 0.819405999 and 0.834930855, respectively. The value of determination was obtained at 97.4%, indicating that the correlation between GDP at constant prices and population with increasing CO emissions in air is very strong. Estimator model obtained has a level of accuracy for forecasting is 0.98478981 or 98.4798981%. Thus, the model estimator obtained is able to describe the actual data pattern.